Resimli-haritalı mufassal Osmanlı tarihi (İstanbul İstanbul İstanbul İstanbul İstanbul İstanbul)
6 cilt (1. c. 608 sayfa ; 2. c. sayfa 611-1182, [4] sayfa ; 3. c. sayfa 1188-1792 ; 4. c. sayfa 1796-2368 ; 5. c. sayfa 2372-2960 ; 6. c. sayfa 2964-3680)